Investigating the role of active citizenship in the relationship between awareness of citizenship rights and accountability and transparency in Rasht Municipality - Basiri Lifshagerd , Maryam (International Journal of Business Management and Entrepreneurship, 2022)
The main purpose of this study was to investigate the role of active citizenship in the relationship between awareness of citizenship rights with accountability and transparency in Rasht municipality. The present study is a descriptive-survey that describes records, analyzes and interprets the existing conditions. The statistical population of the study includes all citizens of the five districts of Rasht municipality, of which 384 were selected based on Krejcie and Morgan tables. Spss24 software was used to collect data from a questionnaire and for data analysis. The results of this study showed that there is a relationship between citizens’ awareness of citizenship rights and active citizenship in five districts of Rasht municipality. There is a relationship between active citizenship and accountability in 5 districts of Rasht municipality. There is a relationship between active citizenship and transparency in the five districts of Rasht municipality. There is a relationship between citizens’ awareness of citizenship rights and accountability in the five districts of Rasht municipality. There is a relationship between active citizenship and transparency in the five districts of Rasht municipality. There is a relationship between citizens’ awareness of citizenship rights and accountability in the five districts of Rasht municipality. There is a relationship between citizens’ awareness of citizenship rights and transparency in the five districts of Rasht municipality.